SOCIO-DEMOGRAPHIC AND LAND USE DETERMINANTS OF NON-COMMUTE TRAVEL GENERATION IN CRACOW, POLAND - Izabela BUCZAK; Paulina GIZA; Aneta JANAS; Andrzej KOSIBA; Katarzyna SOBINEK; Monika RYSAK; Justyna PANICZ; Patrycja PŁANETA; Krzysztof LIPIEŃ; Witold KOGUT; Houshmand E. MASOUMI (Scientific Journal of Silesian University of Technology. Series Transport)
The circumstances of passengers’ decisions and behaviours concerning non-commute urban travels in Eastern Europe is not well-studied; most of the studies on this topic was done on Western societies. This paper presents the results of a study on Cracow, Poland. This study is based on a survey in two neighbourhoods of different urban forms in Cracow, one with central structure with compact land use and the other a representative of socialist urban form with big residential blocks and no central local places. The survey was carried out from January to February 2019 with 426 inhabitants. The results of the Ordinary Least Square models reveal that age, daily activity, the place of shopping, frequency of shopping in the vicinity of homes, and frequency shopping activities outside in farther places are significantly correlated with the frequency of non-work trips in Cracow. The sprawled decentral district produces a high correlation between shopping trips outside the district and the overall nonwork trip frequency, referring to the failure of the socialist urban form to keep non-work trips inside the districts by the presence of local facilities like shops and retail. It is discussed in this paper that such correlations may be very much context-specific, as there are some differences between the findings of this paper and those of international findings in high-income and developing countries.